An experiment was carried out to ascertain the role of propionate on glucose synthesis using eight Brahman steers which were equipped with rumen and abomasal cannulae and fed a basal diet consisted of barley straw ad libitum, 150 g/head/d mineral mix and 500 ml molasses. In addition, 75 g urea dissolved in 1500 ml water was infused continuously to rumen to satisfy the requirement for rumen degradable nitrogen (RDN) using a peristaltic pump. Two animals served as control while the other six recei - Hendrawan Soetanto (Media Veteriner, 1999)
An experiment was carried out to ascertain the role of propionate on glucose synthesis using eight Brahman steers which were equipped with rumen and abomasal cannulae and fed a basal diet consisted of barley straw ad libitum, 150 g/head/d mineral mix and 500 ml molasses. In addition, 75 g urea dissolved in 1500 ml water was infused continuously to rumen to satisfy the requirement for rumen degradable nitrogen (RDN) using a peristaltic pump. Two animals served as control while the other six received, respectively, 100, 150, 200, 250, 400, and 500 g/h/d sodium propionate which were dissolved in urea. Following three weeks adaptation period, an indwelling catheter was inserted into both sides of jugular veins and about 24 hour latter each animal received a bolus injection of 0.3 mCi 2_3H glucose via one of their jugular vein catheter. Blood samples were withdrawn from the other side of the catether at intervals of 30,60, 120, 180, 240, 300 and 360 minutes starting at the onset of 2_3H glucose administration. These samples were then assayed to allow a calculation of glucose entry rate (GER) assuming that the decay of specific radioactivity of 2_3H glucose followed a first order kinetic. The conversion efficiency of propionate to glucose synthesis was calculated by the difference between the increment of GER and the amount of propionate infused. The results showed that propionate infusion was associated with increased glucose entry and utilisation. The highest level of propionate infusion doubled the GER over that of control animals. This suggests that substantial amount of propionate had been converted into glucose. However, the increment in GER could not be accounted fully from the amount of propionate infused suggesting that the endogenous glucose entry varied markedly between animals. The conversion efficiency of propionate to glucose in this experiment ranged from -0.9 to 1.22.